Development research of terminal evaluation system of internet of things - Jinfeng XIE; Hanqi YAN; Bingguang DENG; Yan ZHANG (Dianxin kexue)
Under the large-scale commercial application of internet of things technology, the existing terminal evaluation system can not meet the new requirements of massive, multi-type and multi-form internet of things terminal evaluation.The research on the development of evaluation system for internet of things terminal was carried out, and the suggestions and methods of evaluation system for internet of things terminal were put forward from three dimensions of foundation, application and security, combined with the development trend of testing means, so as to provide reference for future development, promote the quality of IoT terminals, ensure the good interoperability between terminals and networks, and improve the end-to-end service quality.